Upaya Guru PAI dalam Mengembangkan Kemampuan Critical Thinking Siswa di SMPN 40 Takengon - Laili Nazwa Adfiani; Dedi Masri; Muslem Muslem (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This research was motivated by the researcher's interest in the efforts made by PAI teachers to develop students' critical thinking abilities so that students become more active in the learning process. This research uses qualitative methods with a type of field study (field research) through a descriptive qualitative approach. Data collection techniques use observation, interviews and documentation. The analysis was carried out according to experts, namely Milles and Hubberm, through data reduction, data presentation and drawing conclusions and researchers used triagulation as a form of checking the validity of the data obtained. The results of the research show that the critical thinking abilities of class VIII students at SMPN 40 Takengon are good, this can be seen when students are active in asking questions and fulfill the indicator criteria contained in critical thinking. Efforts made by PAI teachers to develop students' critical thinking skills include teachers asking students stimulating questions through a random system, secondly giving opportunities to students, thirdly using group/collaboration methods. Supporting factors for PAI teachers in developing critical thinking skills are cellphones, training/workshops, and teacher creativity. The inhibiting factors include limited time, different student abilities, creating a conducive atmosphere, and limited facilities and infrastructure.